TRANSLATOR'S VOICE IN THE TRANSLATED VERSION OF SIR ARTHUR CONAN DOYLE'S SHERLOCK HOLMES: THE ADVENTURE OF THE NOBLE BACHELOR AND THE ADVENTURE OF THE BLUE CARBUNCLE - Ambarita, Yohanti (2016)
This paper aims to investigate the cases of translator's voice occurred in the Bahasa Indonesia version of Sir Arthur Conan Doyle's Sherlock Holmes: the Adventure of the Noble Bachelor and the Adventure of the Blue Carbuncle. By using qualitative method and content analysis, the data were collected based upon the noun types of Frank (1972), analyzed based upon the translation strategies Vinay and Darbelnet (1957), and the translator's voice were categorized into three cases of Hermans's framework (2010). The findings show that the most frequent noun type is countable/uncountable nouns. In addition, the translator used six translation strategies and the most frequent strategy is adaptation. The strategies mostly represent the cases of Text's Orientation an Implied Reader in the Bahasa Indonesia version of Sherlock Holmes: the Adventure of the Noble Bachelor and the Adventure of the Blue Carbuncle. Findings also show that the translation strategies and cases occur in the translated text express the intervention of the translator.----------- Abstrak: Studi ini bertujuan untuk meneliti kasus-kasus pada translator's voice yang terjadi pada terjemahan Bahasa Indonesia novel Sir Arthur Conan Doyle yang berjudul Sherlock Holmes: the Adventure of the Noble Bachelor and the Adventure of the Blue Carbuncle. Dengan menggunakan metode kualitatif dan konten analisis, data dikumpulkan berdasarkan tipe kata benda yang dikemukakan oleh Frank (1972), dianalisis berdasarkan strategi penerjemahan yang dikemukakan oleh Vinay and Darbelnet (1957), dan translator's voice dikategorikan dalam tiga kasus berdasarkan teori Herman (2010). Temuan menunjukan bahwa tipe kata benda yang paling sering muncul adalah countable/uncountable nouns. Selanjutnya, penerjemah menggunakan enam strategi penerjemahan dan strategi yang paling banyak muncul adalah adaptation. Strategi-strategi tersebut kebanyakan mewakili kasus Text's Orientation an Implied Reader dalam terjemahan bahasa Indonesia dari novel Sherlock Holmes: the Adventure of the Noble Bachelor and the Adventure of the Blue Carbuncle. Temuan juga menunjukkan bahwa strategi- strategi penerjemahan dan kasus-kasus terjadi pada teks terjemahan menyatakan campur tangan penerjemah.